PREPARATION AND PROPERTIES OF COMPOUND ARNEBIAE RADIX MICROEMULSION GEL - Chen, Jing; He, Yanping; Gao, Ting; Zhang, Licheng; Zhao, Yuna (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Compound Arnebiae radix oil has been clinically applied to treat burns and scalds for a long time.However, it is unstable and inconvenient to use. The aim of this study was to prepare a compound Arnebiae radixmicroemulsion gel for transdermal delivery system and evaluate its characteristics.Materials and Methods: Based on the solubility of Shikonin, the active component of Arnebiae radix and the resultsof phase studies, adequate ratio of each component in microemulsion was determined. The optimized microemulsiongel was prepared using Carbomer 940. The gels were characterized in terms of appearance, preliminary stability testand the content of Shikonin in the compound Arnebiae radix microemulsion gel with HPLC analysis.Results: The optimized conditions for preparing microemulsion were Tween-80, glycerin, isopropyl myristate (IPM)with the ratio of 6:3:2. The optimal microemulsion gel was obtained with Carbomer 940 (1.0%).Conclusion: The prepared compound Arnebiae radix microemulsion gel showed good stability over time. It is moreconvenience in application than the previous used formulations.